Tracking Capability and Detection Probability Assessment of Space-Based Automatic Identification System (AIS) From Equatorial and Polar Orbiting Satellites Constellation - Wahyudi Hasbi; Kamirul (IEEE Access)
Performance of LAPAN-A2 and LAPAN-A3 space-based Automatic Identification System (AIS) have been successfully assessed as the satellites operated at individual and two-satellites constellation modes. Since LAPAN-A2 and LAPAN-A3 respectively orbiting at 6° and 97° of inclination, they form a unique constellation; hence, assessment on AIS performance from this equatorial-polar constellation is unprecedented. The assessment is intended to measure both the system and receiver performance of space-based AIS. The measurement of system performance calculates the capability of a space-based AIS system in re-detecting a ship as it moves globally. This performance is used to analyze whether the satellite and its AIS payload are systematically well-configured, including its orbital properties, antenna placement, and receiver’s ability. The measurement of receiver performance is aimed to analyze the receiver capability in detecting all existing ships transmitting the AIS messages. This performance is represented as the ratio between the number of ships detected by the space-based AIS receiver and an ideal AIS receiver. In our case, massive AIS messages collected by an integrated space-terrestrial AIS receiver network has been used as the benchmark. By using 31 days of the collected AIS dataset, operating the satellites as a constellation increases the system and receiver performance by a factor of 7.56% and 7.93%, respectively. The further result shows that the constellated AIS receiver performs excellently in the deep-sea regions, with the value of system performance ranging from 95% to 100%. Moreover, the receivers of constellation satellites overperformed the benchmark receiver on up to 61.84% of their full coverage. The main contribution of this research is to provide information related to the advantages of operating equatorial-polar AIS constellation regarding its in-orbit performance. The results could become a reference in developing a space-based maritime surveillance tool with excellent performance and frequent accesses in those regions.